(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2012)
Notice of Retraction The KEMANUSIAAN the Asian Journal of Humanities herewith announces its decision to retract article “An Appraisal of the Aesthetic Dimension of the African Philosophy of Cloth” (Bridget O. J. Omatseye and Kingsley O. Emeriewen) which was scheduled for publication in Volume 19, No. 1. The decision is made upon discovery that the said article has been submitted and published in another journal. The journal also wishes to reiterate the importance of adherence to its author’s guideline, which specifically outlines that: Manuscripts submitted for publication must be original, previously unpublished (except in the form of an abstract or as part of a published lecture or academic thesis), and not under consideration for publication elsewhere. Its publication must be approved by all Authors and tacitly or explicitly by the responsible authorities where the work was carried out, and that, if accepted, it will not be published elsewhere in the same form, in English or in any other language, without the written consent of the publisher, USM Press.